Investigation of Knowledge, Attitudes and Practices Related to Incontinence-Associated Dermatitis Among Nursing Home Nurses in Shanghai - Yang X; Yang Y; Wang J (Nursing: Research and Reviews, 2025)
Xiaoyan Yang,1,2 Yaping Yang,2 Jing Wang2 1School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China; 2Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of ChinaCorrespondence: Jing Wang, Yangpu Hospital, School of Medicine, Tongji University, 450 Tengyue Road, Yangpu District, Shanghai, People’s Republic of China, Tel +86 13918271059, Email 840518242@qq.comPurpose: The aim of this study was to examine the knowledge, attitudes and practices (KAPs) of current nursing home nurses with regard to incontinence-associated dermatitis (IAD), which has not been studied in China, to provide a theoretical basis for nursing homes to conduct training on IAD and reduce its incidence.Patients and Methods: The KAP model, one of the most commonly used models in medicine, suggests that any practice depends on one’s attitude and knowledge. Following this theory, we designed a questionnaire to investigate IAD-related KAPs among 382 nurses who were recruited via the cluster sampling method from ten Shanghai nursing homes.Results: The IAD-related KAP scores (completion rates) were 50.69± 7.46 (1.05%), 53.67± 7.88 (35.34%) and 45.9± 7.69 (19.90%) points. The IAD-related knowledge scores differed significantly by ability level and professional title (P< 0.05). IAD-related attitudes differed significantly by professional title and ostomy wound-related incontinence group membership status (P< 0.05). IAD-related practice scores differed significantly by ostomy wound-related incontinence group membership status (P< 0.05).Conclusion: Nursing home nurses have positive attitudes towards IAD, but their understanding of IAD is not comprehensive, and their execution in practice is insufficient. The results of this study indicate potential directions for future training.Plain language summary: A self-designed questionnaire was used to investigate IAD-related KAPs among 382 nurses from ten nursing homes in Shanghai. The results revealed that nursing home nurses had a positive attitude towards IAD, but their knowledge was not comprehensive, and their execution was insufficient. These findings provide a theoretical basis for the IAD-related training of nursing home nurses.Keywords: KAP, dermatitis, nursing homes